Developing a codesigned text message-based digital oral health education resource (TOOTH) - Shalinie King; Lauren Adriel Church; Edel O’Hagan; Dion Candelaria; Aboli Pawar; Ashley Cooper; Rebecca Chen; Alice Gibson (Digital Health)
Objective Digital health technologies offer a more equitable way of providing access to health education. This study engaged consumers and clinicians from two Australian regions with a high burden of oral disease to develop a digital oral health resource called “TOOTH” tailored for adults. Methods A total of three focus groups (one clinician and two consumers) were conducted to identify themes that were used to draft text message content. The study team reviewed, refined, and mapped these messages to behaviour change techniques and developed videos to support key concepts. Results Eight multidisciplinary clinicians (dentist, oral health therapist, dietician, cardiac nurse, and dental nurse), 75% female with a mean age of 48 ± 10 years, and seven consumers from a metropolitan and a regional area in New South Wales, 43% female with a mean age 62 ± 11.6 years participated in the focus groups. Key themes identified by clinicians included (1) limited support from medical and allied health teams for integrating oral health care into the healthcare system, (2) government-supported measures enable prevention, and (3) poor oral health of Australians. Consumers highlighted (1) barriers to accessing oral health care, (2) negative attitudes towards oral health, and (3) limited oral health-related knowledge. The final resource developed includes 81 text messages sequenced to ensure a gradual increase in knowledge and skill and five supporting videos. Conclusions The TOOTH resource has the potential to improve awareness and knowledge regarding oral disease prevention, enabling more equitable access to oral health education and better self-management of oral health.